(untitled) - James, Glyn (Wokingham, 1993)
The book contains over 320 fully worked examples and more than 750 exercises, with answers to all the questions given. There are copious review exercises at the end of each chapter and these are designed both to reinforce understanding and to extend the range of topics included.
Keywords: Engineering mathematics